2015
DOI: 10.21653/tfrd.280068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Additional Proprioceptive Neuromuscular Facilitation Over Conventional Therapy In Patients With Adhesive Capsulitis

Abstract: Purpose: This study is performed to investigate the effectiveness of upper extremity and scapula Proprioceptive Neuromuscular Facilitation (PNF) techniques in adhesive capsulitis (AC).Methods: Thirty-six subjects were randomized into two groups. Control group (n=18) was treated with conventional physiotherapy applications consisting of hot-pack and ultrasound, and wall and wand exercises instructed as a home program; study group (n=18) was treated with upper extremity and scapula PNF patterns besides conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
1
10
0
5
Order By: Relevance
“…According to this review physiotherapy seems to be recommended in individuals with primary frozen shoulder. Therapeutic exercise has demonstrated to be an effective option in all outcomes reported, from mobility to function and pain (9,(22)(23)(24)27,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this review physiotherapy seems to be recommended in individuals with primary frozen shoulder. Therapeutic exercise has demonstrated to be an effective option in all outcomes reported, from mobility to function and pain (9,(22)(23)(24)27,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis between two groups showed significant differences favour to experimental group in all parameters except forward flexion. Akbas et al (30) investigated the role of PNF exercises for scapula and arm in addition to home exercises in thirty-six patient. Both groups also received heat packs and ultrasound before their three weeks treatment (fifteen sessions).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, significant group differences were not encountered. Akbaş et al [47] indicated significant effects on night pain and flexion, and abduction ROM values with upper extremity and scapular proprioceptive neuromuscular facilitation (PNF) along with conventional physiotherapy compared to the control group, whereas Balci et al…”
Section: Quality Reviewmentioning
confidence: 99%